Makna Pembinaan Rohani bagi Guru dan Karyawan di Sekolah Kristen: Kajian Fenomenologis tentang Spiritualitas dan Kepuasan Kerja - Martinus Tjahjadi; Christiansen Gabriel; Heryanto Panjaitan; Maria Donata Dona Kwartantri; Corry Limmelda (Magister Teknologi Pendidikan Fakultas Pascasarjana Pendidikan Universitas Pelita Harapan, 2025)
Within Christian educational settings, spiritual formation plays an important role in shaping how employees experience meaning, resilience, and well-being at work. This qualitative phenomenological study explores the lived experiences of teachers and staff regarding spiritual formation in a Christian school and how these experiences shape work meaning and job satisfaction. Data were collected through in-depth interviews with five participants and analysed using phenomenological interpretation. The findings reveal that spiritual formation transforms work into a meaningful calling, strengthens resilience in facing professional challenges, fosters supportive communal relationships, and contributes to job satisfaction beyond material rewards. The study concludes that spiritual formation functions as a foundational experiential process that integrates spirituality, resilience, and job satisfaction within the context of Christian education.